Nitrogen metabolism in cyanobacteria: metabolic and molecular control, growth consequences and biotechnological applications. (3rd September 2018) - Esteves-Ferreira, Alberto A.; Inaba, Masami; Fort, Antoine; Araújo, Wagner L.; Sulpice, Ronan
Abstract: Cyanobacteria are one of the earliest branching groups of organisms on the planet, and during their evolutionary history were submitted to varying selective pressures. Nowadays, cyanobacteria can grow in a variety of conditions, using a large number of nitrogen sources. The control of the nitrogen metabolism in cyanobacteria depends on a fine-tuning regulatory network involving 2-oxoglutarate (2-OG), PII, PipX, and NtcA. This network answers to the cellular 2-OG levels, which reflects the cellular carbon/nitrogen balance, and as an output regulates gene expression, translation, protein activities and thus metabolic pathways. Hence, the diurnal regulation of growth may be directly dependent of this network, as it coordinates the use of photoassimilates towards either growth or the accumulation of reserves, based on the environmental conditions. Therefore, analysis of the nitrogen control network is not only important to comprehend the metabolic control of growth in cyanobacteria, but is also a target to improve cyanobacterial biotechnological potential. In this review, we discuss the mechanisms involved in the control of nitrogen metabolism and its potential role in the diurnal regulation of growth. Then, we highlight why a better understanding of the mechanisms involved in the partitioning of carbon and nitrogen towards growth or storage would increase the biotechnological potential of these organisms.